Nod2 Protects the Gut From Experimental Colitis Spreading to Small Intestine. (30th November 2019) - Al Nabhani, Ziad; Berrebi, Dominique; Martinez-Vinson, Christine; Montcuquet, Nicolas; Madre, Chrystele; Roy, Maryline; Ogier-Denis, Eric; Dussaillant, Monique; Cerf-Bensussan, Nadine; Zouali, Habib; Daniel, Fanny; Barreau, Frédérick; et al.
Abstract: Background and Aims: Nucleotide oligomerization domain 2 [ NOD2] mutations are key risk factors for Crohn's disease [CD]. NOD2 contributes to intestinal homeostasis by regulating innate and adaptive immunity together with intestinal epithelial function. However, the exact roles of NOD2 in CD and other NOD2-associated disorders remain poorly known. Methods: We initially observed that NOD2 expression was increased in epithelial cells away from inflamed areas in CD patients. To explore this finding, Nod2 mRNA expression, inflammation, and cytokines expression were examined in the small bowel of wild-type [WT], Nod2 knockout and Nod2 mutant mice after rectal instillation of 2, 4, 6-trinitrobenzene sulphonic acid [TNBS]. Results: In WT mice, Nod2 upregulation upstream to rectal injury was associated with pro-inflammatory cytokine expression but no overt histological inflammatory lesions. Conversely, in Nod2-deficient mice the inflammation spread from colitis to ileum and duodenum. Conclusions: Nod2 protects the gut from colitis spreading to small intestine.